2019
DOI: 10.1155/2019/7948687
|View full text |Cite
|
Sign up to set email alerts
|

Research Progress on Regulatory B Cells in Systemic Lupus Erythematosus

Abstract: Systemic lupus erythematosus (SLE) is a chronic, systemic, autoimmune inflammatory disease characterized by the production of numerous autoantibodies and cytokines, as well as multiple organ damage. Specific B cell subsets negatively regulate immune responses and have been termed regulatory B cells (Bregs). Bregs are characterized by the production of the immunoregulatory cytokines interleukin (IL)-10, IL-35, and transforming growth factor (TGF)-β. Bregs suppress other immune cells through the secretion of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 48 publications
0
18
0
Order By: Relevance
“…Although various phenotypes of Bregs have been reported, such as CD24 hi CD38 hi , CD24 hi CD27 + , CD25 hi CD71 hi CD73 lo , and CD19 + Tim1 + B subsets, the suppressive functions of Bregs via secretion of IL-10 and IL-35 have highlighted a regulatory role of Bregs in maintaining immune homeostasis in human. Future studies on the impaired inhibitory effects of Bregs may lead to the clinical applications of Breg cell therapy in SLE [163]. Thus, a combination of in vitro expansion of Bregs and adoptive transfer of autologous Bregs may restore the immune regulatory functions of Bregs and effectively suppress effector T cell response in SLE [164].…”
Section: Perspectivesmentioning
confidence: 99%
“…Although various phenotypes of Bregs have been reported, such as CD24 hi CD38 hi , CD24 hi CD27 + , CD25 hi CD71 hi CD73 lo , and CD19 + Tim1 + B subsets, the suppressive functions of Bregs via secretion of IL-10 and IL-35 have highlighted a regulatory role of Bregs in maintaining immune homeostasis in human. Future studies on the impaired inhibitory effects of Bregs may lead to the clinical applications of Breg cell therapy in SLE [163]. Thus, a combination of in vitro expansion of Bregs and adoptive transfer of autologous Bregs may restore the immune regulatory functions of Bregs and effectively suppress effector T cell response in SLE [164].…”
Section: Perspectivesmentioning
confidence: 99%
“…IL-10 as an anti-inflammatory cytokine has the characteristics of cytokines as cytokines T-regulator cells especially T regulator type 1 cells (Tr1) which under normal circumstances can inhibit the response of B cells which is an independent effect of IL-10. IL-10 itself is not only produced by T-reg cells but also produced by other T-helper cells that have regulatory functions, besides IL-10 is also a cytokine that plays a role in the maturation and differentiation factors of B cells, so as to increase survival, proliferation, isotype changes, and B cell differentiation to plasma cells [23], [24].…”
Section: Discussionmentioning
confidence: 99%
“…A study by Su et al demonstrated the involvement of microRNA (miRNAs) in the stimulation of IL-10 in SLE. The dysregulation of miR-199-3p expression increases IL-10 production which targets Poly (ADP-ribose) polymerase-1 which is a serological marker found in SLE patients and is associated with inflammatory factors and cytokines, but the role of miRNA in the pathogenesis of SLE is still being evaluated, especially its impact on the clinical and activity of SLE disease [23], [24], [25], [26].…”
Section: Discussionmentioning
confidence: 99%
“…However, IL-35 secreted by CD4 + CD25 + FOXP3 + regulatory T lymphocytes (Tregs) has a significant immunosuppressive effect in colon cancer and pancreatic cancer and is negatively related to the prognosis of patients ( Zeng et al, 2013 ; Nicholl et al, 2014 ). On the other hand, IL-35 secreted by Breg cells can negatively regulate the immune response of human systemic lupus erythematosus, inhibit the release of a variety of pro-inflammatory cytokines, and slow down the progression of the disease ( Wang et al, 2019b ). In animal experiments, IL-35 produced by activated Breg cells can significantly improve T cell-mediated encephalomyelitis and inhibit the growth of Salmonella in mice ( Shen et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%